Modified loop myopexy technique for severe high myopic strabismus fixus. (15th May 2017) - Zou, Leilei; Liu, Shuai; Liu, Rui; Yao, Jing; Liu, Yan; Lin, Jing; Liu, Hong
Abstract: Importance: This study introduces a modified loop myopexy technique for severe high myopic strabismus fixus. Background: This study aims to evaluate the surgical results of loop myopexy with or without medial rectus recession for the treatment of patients with myopic strabismus fixus. Design: This is a retrospective study in a Chinese teaching hospital. Participants: Data was collected from 25 myopic strabismus fixus patients (33 eyes) with restriction in both abduction and sursumduction. Methods: First, the loop myopexy technique was performed. Following the loop myopexy technique, a medial rectus recession was performed if esotropia remained. If esotropia and/or hypotropia still persisted, second‐stage surgery of the contralateral eye was performed. Main Outcome Measures: The main outcome measures were ocular deviations, eye movements and the angles of dislocation of the globe. Results: At the last follow‐up, mean deviation of esotropia was significantly improved (10 vs. 92 PD; p = 0.000), while mean deviation of hypotropia was improved (6 vs. 32 PD; p = 0.008). Mean abduction limitation was improved (−2.7 vs. −5.0; p = 0.000); mean elevation limitation improved (−3.2 vs. −5.0; p = 0.000). The angle of dislocation of the globe was significantly decreased (103.0 vs. 235.3 D; p = 0.002). Conclusions and Relevance: Modified Yokoyama's surgery effectively corrected the restrictive esotropia and hypotropia, restored the dislocated globe back into the muscle cone and improved the eye movement in severe myopic strabismus fixus.